Fabrication of Superhydrophobic Surface on Low Carbon Steel. Issue 1 (1st July 2022) - Satyarathi, Jitendra; Kumar, Vijay; Kango, Saurabh; Sharma, Nitin; Verma, Rajeev
Abstract: The purpose of the present work is to fabricate superhydrophobic surfaces on commonly used low carbon steel (AISI 1018). Laser surface texturing (LST) method is used for creating circular textures on mild steel surface having the diameter and pitch of 200 μm each. Two different materials (wax & Candle soot) are used to decrease the surface energy of the mild steel. It is observed from the results that the water contact angle of untreated surface increases from 87° to 155° after LST and lowering the surface energy by using wax, followed by candle soot.